Proteomic profiling of a robust Wolbachia infection in an Aedes albopictus mosquito cell line. Issue 3 (22nd September 2014) - Baldridge, Gerald D.; Baldridge, Abigail S.; Witthuhn, Bruce A.; Higgins, LeeAnn; Markowski, Todd W.; Fallon, Ann M.
Summary W olbachia pipientis, a widespread vertically transmitted intracellular bacterium, provides a tool for insect control through manipulation of host–microbe interactions. We report proteomic characterization of wStr, a Wolbachia strain associated with a strong cytoplasmic incompatibility phenotype in its native host, Laodelphax striatellus. In the Aedes albopictus C/wStr1 mosquito cell line, wStr maintains a robust, persistent infection. MS/MS analyses of gel bands revealed a protein 'footprint' dominated by Wolbachia‐encoded chaperones, stress response and cell membrane proteins, including the surface antigen WspA, a peptidoglycan‐associated lipoprotein and a 73 kDa outer membrane protein. Functional classifications and estimated abundance levels of 790 identified proteins suggested that expression, stabilization and secretion of proteins predominate over bacterial genome replication and cell division. High relative abundances of cysteine desulphurase, serine/glycine hydroxymethyl transferase, and components of the α‐ketoglutarate dehydrogenase complex in conjunction with above average abundances of glutamate dehydrogenase and proline utilization protein A support Wolbachia genome‐based predictions for amino acid metabolism as a primary energy source. wStr expresses 15 Vir proteins of a Type IV secretion system and its transcriptional regulator. Proteomic characterization of a robust insect‐associated Wolbachia strain provides baseline information that will inform further development of in vitro protocols for Wolbachia manipulation.